Comparison of sodium content of meals served by independent takeaways using standard versus reduced holed salt shakers: cross-sectional study. Issue 1 (December 2016) - Goffe, Louis; Hillier-Brown, Frances; Doherty, Aoife; Wrieden, Wendy; Lake, Amelia; Araujo-Soares, Vera; Summerbell, Carolyn; White, Martin; Adamson, Ashley; Adams, Jean
Abstract Background Takeaway food has a relatively poor nutritional profile. Providing takeaway outlets with reduced-holed salt shakers is one method thought to reduce salt use in takeaways, but effects have not been formally tested. We aimed to determine if there was a difference in sodium content of standard fish and chip meals served by Fish & Chip Shops that use standard (17 holes) versus reduced-holed (5 holes) salt shakers, taking advantage of natural variations in salt shakers used. Methods We conducted a cross-sectional study of all Fish & Chip Shops in two local government areas (n = 65), where servers added salt to meals as standard practice, and salt shaker used could be identified (n = 61). Standard fish and chip meals were purchased from each shop by incognito researchers and the purchase price and type of salt shaker used noted. Sodium content of full meals and their component parts (fish, chips, and fish batter) was determined using flame photometry. Differences in absolute and relative sodium content of meals and component parts between shops using reduced-holed versus standard salt-shakers were compared using linear regression before and after adjustment for purchase price and area. Results Reduced-holed salt shakers were used in 29 of 61 (47.5 %) included shops. There was no difference in absolute sodium content of meals purchased from shops using standard versus reduced-holed shakers (mean = 1147 mg [equivalent to 2.9 g salt]; SD = 424 mg;p > 0.05). Relative sodium content was significantly lower in meals from shops using reduced-holed (mean = 142.5 mg/100 g [equivalent to 0.4 g salt/100 g]; SD = 39.0 mg/100 g) versus standard shakers (mean = 182.0 mg/100 g; [equivalent to 0.5 g salt/100 g]; SD = 68.3 mg/100 g;p = 0.008). This was driven by differences in the sodium content of chips and was extinguished by adjustment for purchase price and area. Price was inversely associated with relative sodium content (p < 0.05). Conclusions Using reduced-holed salt shakers in Fish & Chip Shops is associated with lower relative sodium content of fish and chip meals. This is driven by differences in sodium content of chips, making our results relevant to the wide range of takeaways serving chips. Shops serving higher priced meals, which may reflect a more affluent customer base, may be more likely to use reduced-holed shakers.